UJI HERITABILITAS GAHARU (AQUILARIA MALACCENSIS LAMK) UMUR EMPAT TAHUN PADA DEMPLOT DINAS KEHUTANAN KABUPATEN KETAPANG (Test of Heritability of (Aquilaria malaccensis Lamk) For Four Years on The Forestry Agency of Regency Ketapang) - Erwi, Lidwina; Muin, Abdurrani; hanuddin, Bur (Universitas Tanjungpura, 2015)
Agarwood’s is a product of non timber forest products in the form of lumps, flakes or powder have a distinctive fragrance aroma emanates from the womb chemicals of gubal. The benefits of Aloe for deodorizers, room, body cosmetics, medicines and simple. The stands are agarwood (Aquilaria malaccensis Lamk) in natural forests declined due to logging is done in vain, so type A.malaccensis entered in Appendik II of CITES (Convention On International Trade In Endangered Species). To support the efforts of the conservation and sustainability of production, as well as anticipate the development of value to the market and demand continues to increase, the need to perform planting and cultivation. But this time, high-quality agarwood trees not yet available so that required good quality seeds. Seeds like this can be obtained by using seeds from the tree stem through the process of glorification (test line). One that could serve as the seed-producing trees, the forest is the agarwood (Aquilaria malaccensis) contained in Demplot Forestry District Office of Ketapang. But to point the tree seed producer, should begin by doing a test descent. The problem to date, yet gleaned information genetic properties of the agarwood tree. So that needs to be done heritabilitas/test type a. ardesiacus in Demplot Forestry District Office of Ketapang. This research aims to know the: (1) genetic variation of tree diameter and height added a. ardesiacus; (2) the value of the heritabilitas family on the character height and diameter of plant; (3) genetic traits observed among all the test of a. ardesiacus. The results of the study, expected to be material to obtain tree seed-producing qualified as a superior especially in order planting Aloes in the future. This research uses experimental methods in the form of factorial with Randomised Complete Block Desing then with Deuteronomy as much as 5 blocks and each block consists of 10 families, with 5 number of trees exist, so treeplot 250. The results showed the plant A.malaccensis aged 4 years in demplot showed variation in the nature of plant height and diameter. Variation characteristics of high properties and properties/diameter of the plant is affected by genetic factors as high as estimates the value of heritabilitas to the nature of the height and diameter of the value above 0.8. Based on those results, the selection may be made at Demplot Department of Forestry to locate seeds as a source tree plus with the desired properties criteria. The genetic correlation between height and diameter of the plants shown through analysis of correlation regression, show a positive. The positive correlation show that every high added value added is always followed by the diameter of the plant. Keyword : Test of heritability, A.malaccensis.